2017
DOI: 10.1177/1591019917720805
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ruptured blood blister aneurysms using primary flow-diverter stenting with considerations for adjunctive coiling: A single-centre experience and literature review

Abstract: Objective The objective of this article is to conduct a single-centre evaluation and quick literature review of the effectiveness of primary flow-diverter (FD) treatment of ruptured blood blister aneurysms (BBAs), with additional relevance of adjunctive coiling. Methods Patients presenting with subarachnoid haemorrhage (SAH) due to ruptured BBAs and subsequently treated with FDs were retrospectively select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…The primary goal of early intervention is to prevent rebleeding. Although we did not find a significant difference in rebleed rates between aneurysms treated with or without additional coiling, Yang et al showed that adjunctive use of coiling achieves a higher incidence of immediate complete occlusion of blister-like aneurysms 26. However, Mokin et al found no difference in complete (blood blister-like) aneurysm occlusion regarding the use of adjunctive coiling 29.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The primary goal of early intervention is to prevent rebleeding. Although we did not find a significant difference in rebleed rates between aneurysms treated with or without additional coiling, Yang et al showed that adjunctive use of coiling achieves a higher incidence of immediate complete occlusion of blister-like aneurysms 26. However, Mokin et al found no difference in complete (blood blister-like) aneurysm occlusion regarding the use of adjunctive coiling 29.…”
Section: Discussioncontrasting
confidence: 71%
“…Several other series (not in the meta-analysis) investigating FD treatment in the acute SAH phase have been published 9 10 13 19 23–27. The pooled favorable clinical outcome (mRS 0–2) rate of these studies was 71% (range 27–92%) (57/80).…”
Section: Discussionmentioning
confidence: 99%
“…However, FDDs also have the disadvantages of a low initial obliteration rate and early rebleeding. Adjunctive use of coiling can achieve a higher incidence of immediate occlusion of BLAs [ 22 ]. Moreover, dual anti-platelet therapy is another challenging factor for the use of FDDs in the acute phase of aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…Several EVT, microsurgical and hybrid treatment approaches have been published although there is still no consensus on the optimal treatment strategy. [1][2][3][4][5]7,11,[20][21][22][23] Endovascular options can be categorized as either deconstructive (e.g. PVO) or reconstructive (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of these lesions is complicated and various treatment approaches, both endovascular and microsurgical, have been proposed. [1][2][3][4][5][6][7][8][9][10][11][12] Despite significant progress in endovascular and microsurgical treatment, no reliable management strategy has been established so far.…”
Section: Introductionmentioning
confidence: 99%